Relationship between selected demographic factors and secondary school teachers' job satisfaction in Bangladesh - Chowdhury, Mamataz Sharmin; Lope Pihie, Zaidatol Akmaliah; Foo, Say Fooi; Asimiran, Soaib (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The purpose of this study was to investigate the levels of job satisfaction and to determine the effect of demographic factors on levels of satisfaction among secondary school teachers in Bangladesh. The study utilized a descriptive correlational research design. Job satisfaction instrument by Spector (1997) was sent to 367 participants. Data was analyzed using descriptive statistics. independent t-test and ANNOVA. The teachers were moderately satisfied with their job. The construct work itself was ranked highest and benefit was ranked as the lowest of the examined constricts. The findings of this study revealed that no significant difference was found in the job satisfaction based on gender and education. The other two demographic variables age and year of experience at current organisation do influence the level of jobs satisfaction. The result of the study can help teachers and administrators to take action to increase the satisfaction level teachers.